Appaloosa [videorecording (DVD)] - Harris, Ed, 1950-; Irons, Jeremy, 1948-; Mortensen, Viggo, 1958-; Zellweger, Renée, 1969-; Parker, Robert B., 1932-2010 (Warner Home Video, 2009)
1880s, the American West. Randall Bragg is a rich landowner who is wanted for murdering the town marshal. Lawman Virgil Cole and his deputy Everett Hitch are two friends who are hired to defend a lawless town from the murderous rancher. Their efforts become complicated and their friendship is tested when a young widow arrives in town.